Advanced IoT technologies and applications in the industry 4.0 digital economy - Khang, Alex; Abdullayev, Vugar; Hahanov, Vladimir; Shah, Vrushank Manharlal 1985- (CRC Press, 2024)
"The application of IoT technologies and AI-enabled IoT solutions has gradually become accepted by business and production organizations as an effective tool for automating several activities effectively and efficiently and developing and distributing products to the global market. Within this book, the reader will learn how to implement IoT devices, IoT-equipped machines, and AI-equipped IoT applications using models and methodologies along with an array of case studies"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 22, 2024)
Keywords: Internet of things -- Industrial applications; Industry 4.0; Internet of things; Internet des objets; Industrie 4.0; Internet des objets; Applications industrielles; TECHNOLOGY / Robotics